Influência do teor de carbono na formação de austenita retida no aço 43XX - LIMA, Eduarda Santos (133, 2017)
A aplicação dos aços da família 43XX é de suma importância para as indústrias aeroespacial e automobilística, sendo o aço 4340 o mais aplicado, devido a sua alta usinabilidade e temperabilidade. Normalmente são tratados termicamente para alterar suas propriedades mecânicas, sendo o processo de têmpera aplicado para o aumento de dureza a partir da transformação da fase austenita em martensita e o revenimento utilizado para aliviar as tensões internas, causadas pela têmpera. Entretanto, está presente, também, a austenita retida ou residual, resultante da não transformação completa, ou seja, a linha de fim de transformação (Mf) não é ultrapassada. Esta fase aumenta a tenacidade do material, podendo retomar um aumento de dureza durante o trabalho mecânico. Neste trabalho foram realizados os tratamentos térmicos de têmpera e revenimento, seguidos da caracterização microestrutural, buscando identificar as fases presentes, com o objetivo de verificar a influência do teor de carbono na formação de austenita retida. Pode-se concluir que, com o aumento do teor de carbono nas amostras de aço 43XX utilizadas nesta pesquisa, cresceu a porcentagem de austenita retida presente. The application of the 43XX family steels is of great importance for the aerospace and automotive industries, being 4340 steel the most applied due to its high machinability and hardenability. They are usually heat-treated to change their mechanical properties, being the tempering process applied for the increase of hardness from the transformation of the austenite phase to martensite and the tempering used to relieve internal tensions caused by tempering. However, the arrested and residual austenite is also present, resulting from complete non-transformation, that is, the transformation end line (Mf) is not exceeded. This phase increases the toughness of the material and may resume a hardness increasing during the mechanical work. In this work, the tempering and tempering treatments were carried out, followed by the microstructural characterization in order to identify the influence of the carbon content on the formation of retained austenite. It can be concluded that, with the increase of carbon content in the 43XX steel samples used in this research, the percentage of retained austenite increased.

The application of the 43XX family steels is of great importance for the aerospace and automotive industries, being 4340 steel the most applied due to its high machinability and hardenability. They are usually heat-treated to change their mechanical properties, being the tempering process applied for the increase of hardness from the transformation of the austenite phase to martensite and the tempering used to relieve internal tensions caused by tempering. However, the arrested and residual austenite is also present, resulting from complete non-transformation, that is, the transformation end line (Mf) is not exceeded. This phase increases the toughness of the material and may resume a hardness increasing during the mechanical work. In this work, the tempering and tempering treatments were carried out, followed by the microstructural characterization in order to identify the influence of the carbon content on the formation of retained austenite. It can be concluded that, with the increase of carbon content in the 43XX steel samples used in this research, the percentage of retained austenite increased.
Influence of carbon content on the formation of retained austenite in 43XX steel
Keywords: Têmpera; Tratamento térmico; Controle e Processos Industriais